Validation of the Chinese version of the PHQ-15 in a tertiary hospital. Issue 1 (December 2016) - Zhang, Lan; Fritzsche, Kurt; Liu, Yang; Wang, Jian; Huang, Mingjin; Wang, Yu; Chen, Liang; Luo, Shanxia; Yu, Jianying; Dong, Zaiquan; Mo, Liling; Leonhart, Rainer
Abstract Background This study aimed to investigate the reliability and validity of the Chinese version of the Patient Health Questionnaire (PHQ-15) in a tertiary hospital. Methods Using a cross-sectional study design, the Chinese version of the PHQ-15 was administered to a total of 1329 inpatients. To examine the discriminant validity of this questionnaire, we investigated the correlation of the PHQ-15 score with sociodemographic data and the PHQ-9 and GAD-7 scale scores. Exploratory factor analysis was performed to assess the internal consistency of the PHQ-15. To evaluate the consistency of this questionnaire with item response theory (IRT), IRT analysis was performed. Results The Chinese version of the PHQ-15 showed good reliability (Cronbach's alpha = 0.83). The correlations of the PHQ-15 scores with the PHQ-9 depression scale scores (r  = 0.565) and the GAD-7 anxiety scale scores (r  = 0.512) were moderate; these results suggested that the PHQ-15 had discriminant validity. We identified three factors, referred to as "cardiopulmonary, " "gastrointestinal, " and "pain/neurological, " which explained 56 % of the total variance. A second-order factor analysis including these three factors produced an acceptable model. Several items (4, 8 and 11) displayed extreme floor effects. Additionally, item 4 displayed a very small variance of 0.35 and showed very small differences in its thresholds based on IRT analysis. Conclusions The PHQ-15 scale had good reliability and high validity to detect patients with high somatic symptom severity in a Chinese tertiary hospital. Several of the current findings were consistent with previous research on the PHQ-15 in Western countries and in China. To improve the diagnostic quality of this questionnaire, items 4, 8 and 11 can be omitted.